Prosecturs as crime creators: the case of prenatal drug use - Maschke, Karen J. (Criminal justice review, 1995)
This article examines prosecutors' adoption of the crime creator role in matters surrounding prenatal drug use. By interpreting substantive criminal statutes expansively, prosecutors attempted to criminalize women's prenatal behavior. Their crime creation activities were carried out against the backdrop of the war on drugs and the contemporary child protection movement. Although the courts rejected prosecutors' attempts to criminalize prenatal drug use, questions remain about whether this social problem should be criminalized. Moreover, prosecutors' crime creation activities raise questions about the appropriate use of discretionary authority and reveal the tensions between the desire to convict and the obligation to seek justice